Personality of the author and the image of the genres of photojournalism - Shimolin, Victor I. (Journal of the Belarusian State University. Journalism, 2019)
The problems of the relationship between the photojournalist and the heroes of his publications are considered. The role and importance of ethical norms in the constant professional activity are analyzed. It is proved that the cultural level of a specialist determines not only the possession of scientific theory, but also the internal culture, the application in practice of ethical norms. The obtained results allow to conclude that the author’s personality is reflected in the context of his visualverbal works.
Keywords: genre; ideology; personality; position; morality; patriotism; journalism; photography; photojournalism; photo essay